2017
DOI: 10.1515/sgem-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Application of Long Expansion Rock Bolt Support in the Underground Mines of Legnica–Głogów Copper District

Abstract: Abstract:In the underground mines of the Legnica-Głogów Copper District (LGOM) the main way to protect the room excavation is the use of a rock bolt support. For many years, it has proven to be an efficient security measure in excavations which met all safety standards and requirements. The article presents the consumption of the rock bolt support in the Mining Department "PolkowiceSieroszowice" in the years 2010-2015 as well as the number of bolt supports that were used to secure the excavations. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Sci. 2019, 9, 3173 4 of 19 According to Equations (2) and (4), the RMD function is expressed as follows:…”
Section: Rmd Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci. 2019, 9, 3173 4 of 19 According to Equations (2) and (4), the RMD function is expressed as follows:…”
Section: Rmd Functionmentioning
confidence: 99%
“…For example, Zheng et al [2] applied borehole pressure relief technology to prevent rockburst in deep-buried mine roadways and achieved good results. Skrzypkowski et al [3,4] studied a new type of bolt support system, which had good energy absorption and rockburst prevention ability under the condition of tremor. However, in addition to finding reliable prevention and control measures, it is also important to establish an accurate rockburst prediction model in order to resist the occurrence of rockburst disasters [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…2, 3). For all free bolts, the diameter of smooth rod was 0.0183 m. A detailed description of used rock bolts can be found in the literature [22,23]. In order for laboratory studies to best satisfy mining conditions, dual bushings filled with concrete with a compressive strength of at least 75 MPa were used at the laboratory test facility.…”
Section: Laboratory Test Facilitymentioning
confidence: 99%
“…In recent decades, many scholars carried out lots of laboratory and numerical tests, complemented by theoretical analysis, to study the mechanism of anchored rock. In roadway support, the anchor housing is often installed in sections over a short section with one resin charge or using an expansion head [6,7]. Carranza-Torres [8] proposed a closed-form solution of rockbolt reinforcement around tunnels, and numerical analysis confirmed that the bolt plays an important role in increasing the tunnel confining pressure and controlling the surrounding rock deformation.…”
Section: Introductionmentioning
confidence: 99%